The position of language and literature in Islam - Abd. Rahman, Akmal Khuzairy (International Institute of Islamic Thought East and South East Asia & International Islamic University Malaysia, 2016)
The article discusses about the Islamic perspective on language studies and literature from the various proponents of the Islamization movement.